Sustainability: The Challenges and the Promise - Mitchell, George (Maine Policy Review, 2012)
Senator George J. Mitchell’s Margaret Chase Essay reflects on sustainable development. He discusses how teams of Maine faculty and students are working in partnerships across business, government and non-governmental organizations to seek solutions for a wide range of ecological and economic challenges.
Keywords: Maine; sustainability; development